2020
DOI: 10.1177/0002716219896259
|View full text |Cite
|
Sign up to set email alerts
|

Firearm Availability and Fatal Police Shootings

Abstract: Do states with more guns have higher rates of fatal police shootings? This article uses a validated measure of firearm availability (the percentage of suicides committed with a firearm) to examine the relationship between gun proliferation and fatal police shootings. It expands on existing research to include (1) measures of access to Level I and II trauma centers, (2) interpretation of the findings from the lenses of “statistical prediction,” and (3) tests for structural differences between models for black d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…This is highly unlikely to be true . Indeed, the evidence that gun prevalence in a state is associated with higher rates of lethal force by police (even controlling for homicide rates) suggests that police may be more fearful and shoot quicker when they are more likely to interact with an armed individual (Nagin forthcoming). Presumably, criminals would respond in a similar fashion, leading them to arm themselves more frequently, attack more harshly, and shoot more quickly when citizens are more likely to be armed.…”
Section: The Impact Of Rtc Laws: Theoretical Considerations and Simplmentioning
confidence: 99%
See 1 more Smart Citation
“…This is highly unlikely to be true . Indeed, the evidence that gun prevalence in a state is associated with higher rates of lethal force by police (even controlling for homicide rates) suggests that police may be more fearful and shoot quicker when they are more likely to interact with an armed individual (Nagin forthcoming). Presumably, criminals would respond in a similar fashion, leading them to arm themselves more frequently, attack more harshly, and shoot more quickly when citizens are more likely to be armed.…”
Section: The Impact Of Rtc Laws: Theoretical Considerations and Simplmentioning
confidence: 99%
“…The presence of more guns on the street can complicate the job of police as they confront (or shy away from) armed citizens. Daniel Nagin finds a pronounced positive association between statewide prevalence of gun ownership and police use of lethal force (Nagin forthcoming). A Minnesota police officer who stopped Philando Castile for a broken taillight shot him seven times only seconds after Castile indicated he had a permit to carry a weapon because the officer feared the permit holder might be reaching for the gun.…”
Section: The Impact Of Rtc Laws: Theoretical Considerations and Simplmentioning
confidence: 99%
“…I believe a lot can be gleaned from Schwartz and Jahn’s article, and agree that “place-specific policy contexts are likely a major cause of the distribution of overall incidence rates.” The authors specifically mention “state and local firearm regulations, levels of segregation and policy drivers of those levels, or differences in police training and police department protocols.” Daniel Nagin, for example, uncovered a “correlation between statewide prevalence of gun ownership and fatal police shootings for both all decedents and unarmed decedents,” and confirmed that “greater access to trauma centers is associated with lower rates of citizen deaths” [ 68 ]. In a separate study, Jay Jennings and Meghan Rubado showed that agencies requiring officers to file a report when they point their firearms at people experience significantly lower rates of fatal police shootings [ 69 ].…”
Section: Where To Go From Here?mentioning
confidence: 99%
“…The use of force is higher in neighborhoods that are poorer (Smith, 1986) have high rates of crime (Klinger et al., 2016), or are perceived to be less safe (Kahn et al., 2017). Research has also shown that police shooting deaths are higher in states with a higher prevalence of gun ownership (Hemenway et al., 2019; Nagin, 2020). Another important predictor of police violence is the racial makeup of community.…”
mentioning
confidence: 99%